CRUSTAL VELOCITY STRUCTURE UNDER THE RUKSA SEISMIC ARRAY (KARELIA, RUSSIA) - Aleshin I.M.; Kosarev G.L.; Riznichenko O.Yu.; Sanina I.A. (My University, 2006)
Based on data of three three-component seismographs belonging to the temporary small-aperture Russian Karelia Seismic Array (RUKSA) in the Petrozavodsk region (Karelia), a 1-D velocity model of the crust is constructed by the method of the receiver function. Waveforms of distant earthquakes recorded by short-period instruments with improved characteristics are used. The data were inverted by the simulated annealing method. The inversion was stabilized by using phase velocities of Rayleigh waves and traveltimes of converted Ps waves from the 410-km boundary determined from broadband records of the SVEKALAPKO seismic array. Anomalously low seismic velocities are discovered in the upper part of the cross section beneath the RUKSA array.
Keywords: EARTH''S CRUST; SMALL APERTURE ARRAY; METHOD OF THE RECEIVER FUNCTION